Anthropometric measurements for detecting low birth weight - Kusharisupeni Kusharisupeni; Wahyu Kumia Y. Putra; Engkus Kusdinar Achmad (Indonesian Pediatric Society Publishing House, 2013)
Background In several provinces of Eastern Indonesia, the majority of births take place at home (60%) and are assisted by traditional birth attendants. Most of these newborns do not have their birth weight recorded, due to lack of available weighing scales or lack of skill to perform the measurement, especially in rural areas. As such, an early iden tification oflow birth weight cases is needed to prevent infan t morbidity and mortality. Objective To assess anthropometric measurements including calf, chest, and h ead circumferences as a method of choice for detecting low birth weight, as substitute for actual weighing. Methods This cross-sectional study was performed at Banjar Barn, South Kalimantan, Indonesia, from January to March 2012. Subjects were full term, singleton, and live-born infants during the study period, and obtained from private clinics by a purposive sampling procedure. Calf, chest, and h ead circumferences were measured to identify the most suitable substitute for birth weight using Pearson's correlation, ROC, sensitivity, and specificity. Results In this study, a correlation was shown between birth weight and all anthropometric measurements. Optimal calf, chest, and head circumference cutoff points to identify low birth weight infants were 10.3 cm, 30. 7 cm, and 3 1.2 cm, respectively. The area under the curves (AUC) showed good accuracy for all measuremen t types. Calf circumference had the closest estimated true prevalence to the true prevalence (8.52% and 8.6%, respectively) compared to the other measurement types. Conclusion Calf circumference is the most suitable measurement as a substitute for birth weight, due to its estimated true prevalence.